Lead‐Free Halide Double Perovskites: Structure, Luminescence, and Applications. Issue 3 (13th December 2020) - Wu, Ye; Li, Xiaoming; Zeng, Haibo
Abstract : Organic–inorganic halide perovskites have attracted extensive attention due to their excellent optoelectronic properties. However, the toxicity of heavy atom Pb 2+ and instability overshadow further commercial applications, motivating researchers to explore alternative analogues to overcome these disadvantages. Lead‐free halide double perovskites (HDPs), sharing similar crystal structures with organic–inorganic halide perovskites, are promising candidates for optoelectronic applications. However, HDPs possess unique properties that are uncommon in organic–inorganic halide perovskites deriving from feasible component engineering and strong electron–phonon interaction. Bright luminescence in HDPs originates from self‐trapped excitons (STEs) and sensitized dopants can cover the full visible and near‐infrared ray (NIR) gamut by modulating parity‐forbidden transitions and the energy‐transfer process. The superior optoelectronic characteristics of HDPs further extend applications on self‐assembly, white‐light phosphors, NIR bioimaging, and scintillators, in comparison to organic–inorganic halide perovskites. Herein, the structural diversity, tunable luminescence, photophysical mechanism of STEs, charge‐carrier dynamics, size effect, and stability issues of HDPs are discussed. The challenges and outlook for further investigations are also given, which may help in discovering new analogues and boosting the photoluminescence quantum yield and stability of HDPs. Abstract : Herein feasible component engineering for tunable optoelectronic properties of lead‐free halide double perovskites (HDPs) is highlighted. The possible photophysical mechanism of broad emission from self‐trapping states, origin of parity‐forbidden transition, and approaches to boost the optoelectronic performance of HDPs are also summarized. Recent progress in applications on self‐assembly, white light–emitting diodes, near‐infrared imaging, and scintillators is also discussed.